The effect of bone turnover on bone quality and material properties - Kennedy, Oran D. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2008)
Coined in French in the 1820s as a description of a pathological state of bone tissue, the term osteoporosis made its way into the English language only in the 20th century. Unlike other medical concepts, which have not been substantially altered by progress in medical research, the definition of osteoporosis has constantly reflected the state of knowledge on the phenomenon itself (Schapira and Schapira, 1992). Over its 180 years of evolution, this definition has continuously sought to maintain a balance between physiological and clinical criteria. At present the definition, established by the National Institutes of Health (NIH) in 2000, describes osteoporosis as 'a skeletal disorder characterised by compromised bone strength predisposing to an increased risk of fracture'.
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin